1982
DOI: 10.1007/bf01531614
|View full text |Cite
|
Sign up to set email alerts
|

Description of semantic ? Syntactic relations in an autistic child

Abstract: This longitudinal study investigated the language acquisition strategies employed by an autistic child learning sign language. The child's core vocabulary and developing semantic-syntactic relationships were compared with language acquisition in normal children. There were specific deviations in language development noted, in spite of providing the child with appropriate sign language training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

1983
1983
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…''Mute'' was used in four 30,58,63,68 and ''nonverbal'' in one, 22 whereas others reported that their participants exhibited ''unintelligible verbalizations,'' 41 ''no verbal or gestural communication,'' 73 and a ''lack of speech.'' 27 However, these descriptions did not always indicate that the subjects exhibited no speech before treatment.…”
Section: Sign Languagementioning
confidence: 99%
See 2 more Smart Citations
“…''Mute'' was used in four 30,58,63,68 and ''nonverbal'' in one, 22 whereas others reported that their participants exhibited ''unintelligible verbalizations,'' 41 ''no verbal or gestural communication,'' 73 and a ''lack of speech.'' 27 However, these descriptions did not always indicate that the subjects exhibited no speech before treatment.…”
Section: Sign Languagementioning
confidence: 99%
“…Two subjects were reported to be able to follow simple verbal directions. 58,73 Treatment intensity varied from case to case. The total length of treatment ranged from 3 months 30 to more than 5 years, 68 with the majority of students receiving sign language instruction for 1 year or more.…”
Section: Sign Languagementioning
confidence: 99%
See 1 more Smart Citation
“…The methods and analyses used were based on McCarthy (1930), and they revealed that the child's utterances grew in length and his vocabulary increased over the first 6-month period at a rate comparable to that of normal children, but after that point there was no further growth and the child remained at a 30-month level. In a more recent paper, Layton and Baker (1981) reported on an 8-year-old mute autistic boy who was studied over a period of 18 months during which time he was trained in sign language. He too learned a core vocabulary and progressed from single signs to two-word signs, however his use of language was very limited and was restricted in semantic range.…”
mentioning
confidence: 99%
“…Further, many of these children show only limited gains in spoken language in spite of intensive operant therapy (Mack, Webster, & Gokcen, 1980 (Bonvillian & Nelson,. 1976;Carr, , 1982aKiernan, 1977;Layton & Baker, 1981; Creedon, Note 1) and this type of training has achieved widespread use nationally (Goodman, Wilson, & Bornstein, 1978;Lloyd, 1980). A review of the research literature on sign training with handicapped children (Carr, 1979) indicated, however, that although most studies reported positive outcomes, and some were data based, almost none involved controlled experimentation.…”
mentioning
confidence: 99%